Global perspectives on institutionalizing land value capture for sustainable infrastructure planning and innovative fiscal solutions in Indonesia - Pradana, Raiehan Andhika; Nayottama, Muhammad Rasendria; Arundati, Parahita Janu (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: Indonesia faces a significant fiscal challenge in funding infrastructure development, marked by a high debt-to-GDP ratio and interest burden that consumes a large portion of the national budget. This paper examines the institutionalization of Land Value Capture (LVC) as a sustainable and equitable alternative to conventional financing. Methods: The study conducts a comparative analysis of LVC implementation models in Hong Kong, the UK, and India, reviewing existing literature and policy reports. These models, ranging from property-based schemes in Hong Kong to tax-based approaches in the UK and national policies in India, reveal how LVC can capture the increase in land value resulting from public infrastructure projects. Findings: The findings demonstrate LVC's potential to internalize the positive externalities of infrastructure development, aligning with classical economic theories and the principle of fiscal justice. By doing so, it can expand the non-tax state revenue base, reduce debt dependency, and strengthen fiscal resilience. Conclusion: This paper concludes that establishing a robust legal framework, integrating LVC with spatial planning, and fostering public-private collaboration is essential. Novelty/originality of this article: The originality of this research lies in its comprehensive comparative analysis of global LVC models, and the formulation of integrated policy recommendations specifically tailored to Indonesia's unique institutional and fiscal context.